2022
DOI: 10.52547/unmf.20.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Usability of Drug Abuse Registration System From the Users' Point of View at Urmia University of Medical Sciences, Iran

Abstract: Background & Aims: Development of the registry system for substance abuse poisoning may be useful in the systematic collection of information, prevention of poisonings, identification of people and monitoring them, ease of access to information, and decision-making in allocating resources. Evaluation of usability of information systems is one of the most important ways to improve disease registration programs. The purpose of this study was to evaluate the usability of drug abuse registration system from the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The results of Almasi et al's research mainly showed the positive effects of the HIS on the development of health services (30). Additionally, a study conducted in 2020 using the opinions of internal managers and information technology specialists of hospitals affiliated with Urmia University of Medical Sciences showed that the design and implementation of the health information management dashboard should be reviewed and revised (31).…”
Section: Discussionmentioning
confidence: 99%
“…The results of Almasi et al's research mainly showed the positive effects of the HIS on the development of health services (30). Additionally, a study conducted in 2020 using the opinions of internal managers and information technology specialists of hospitals affiliated with Urmia University of Medical Sciences showed that the design and implementation of the health information management dashboard should be reviewed and revised (31).…”
Section: Discussionmentioning
confidence: 99%
“…The problems caused by the dashboard's lack of usability, such as the display of false and ambiguous messages and feedback lacking important information, confuse users and reduce the dashboard's and service delivery's efficiency and quality [35]. As a result, by performing the evaluation, it is possible to identify the problems in the dashboards and take action and plan to solve them to increase the level of user satisfaction and the quality of the dashboard and take steps toward its improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the European Union, the Monitoring Center for Drugs and Addiction (EMCDDA) has been established to provide real, objective, reliable and comparable information about drugs, drug addiction and their consequences (11). Substance abuse has long been recognized as a national problem in Iran that poisoning with pharmaceutical drugs, opioids and alcohols is common (12). According to the statistics of the World Health Organization, 1% of the Iranian population aged 15 or older suffered from alcohol consumption disorders in 2016 (13).…”
Section: Introductionmentioning
confidence: 99%
“…This important matter is implemented by creating information systems and disease registration system (16-17). The disease registration system is the systematic collection of uniform data on a speci c disease, exposure to hazardous substances or events and treatment (12). The purpose of this systems is to investigate disease outbreaks, determine temporal and spatial trends, monitor safety and harm exposures, evaluate the quality of healthcare services, and nally develop and promote research, implement detailed plans and programs (18).…”
Section: Introductionmentioning
confidence: 99%